Expanding the knowledge about the occurrence of anurans in the highest amphibian diversity area of Atlantic Forest: Parque Estadual da Serra do Mar, Sao Paulo, Brazil - Silva, Fernando Rodrigues da; Lyra, Mariana Lucio [UNESP]; Baptista Haddad, Celio Fernando [UNESP]; Rossa-Feres, Denise de Cerqueira [UNESP] (Revista Biota Neotropica, 2017)
The vegetation cover in the Atlantic Forest has been converted to human use or degraded by human activities, which declined the vegetation to 16% of its original extent. Although several protected areas have been created in this Neotropical biome over the past decades, our knowledge of the amphibian species within these areas is still far from adequate. Here, we present lists of anuran species from three different areas of Parque Estadual da Serra do Mar: nucleos Curucutu, Santa Virginia and Sao Sebastiao. To survey anuran species, we visited six sampling units (two ponds, two streams and two trails inside forest fragments) in each locality. Samplings were accomplished from December 2014 to February 2015, December 2015 to February 2016 and December 2016 to February 2017, totalizing 27 days of field samplings in each sampling unit. We recorded 34 anuran species in the Nucleo Curucutu, 44 species in the Nucleo Sao Sebastiao and 42 species in the Nucleo Santa Virginia, totalizing 65 species belonging to 12 families (number of species in parentheses): Bufonidae (5), Brachycephalidae (6), Centrolenidae (1), Craugastoridae (1), Cycloramphidae (2), Hemiphractidae (1), Hylidae (29), Hylodidae (3), Leptodactylidae (12), Microhylidae (2), Odontophrynidae (2), and Phyllomedusidae (1). We hope that these lists can be useful for future studies as well as helping in the management and conservation planning of these protected areas.
Keywords: Amphibians; Biodiversity; Conservation; Hotspots; Species list